2018
DOI: 10.7150/ijms.24170
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dextrose prolotherapy on contusion-induced muscle injuries in mice

Abstract: Current treatment options for muscle injuries remain suboptimal and often result in delayed/incomplete recovery of damaged muscles. In this study, the effects of dextrose prolotherapy on inflammation and regeneration of skeletal muscles after a contusion injury were investigated. Mice were separated into five groups, including a normal control (NC), post-injury with no treatment (mass-drop injury, MDI), post-injury with 10% dextrose (MDI + 10% dextrose), post-injury with 20% dextrose (MDI + 20% dextrose), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Desmin is an intermediate filament protein that connects the Z-line to the mitochondria, the nucleus, and the cell membrane, and its role is mainly to limit the excessive involvement of sarcomeres in muscle contraction and relaxation [2931]. Collagen I is one of the main types of collagen in muscle tissue, and the gap between the stumps after muscle injury is initially filled with hematoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…Desmin is an intermediate filament protein that connects the Z-line to the mitochondria, the nucleus, and the cell membrane, and its role is mainly to limit the excessive involvement of sarcomeres in muscle contraction and relaxation [2931]. Collagen I is one of the main types of collagen in muscle tissue, and the gap between the stumps after muscle injury is initially filled with hematoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we similarly applied prolotherapy to enthesis in our study. It has also been shown that prolotherapy is effective in the repair of muscle injuries 23 . Similarly, prolotherapy was shown to be beneficial in improving muscle damage and regeneration in this region in our study.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies using animal models have suggested that dextrose injection results in stimulation of the inflammatory response, 10 increased ligament size, 11 restored cartilage matrix, 12 and increased desmin protein levels in injured muscle. 13 Most recently, the chondrogenic and antinociceptive effects of dextrose prolotherapy have been demonstrated. [14][15][16] Dextrose prolotherapy has been considered an injection-based complementary and alternative medical therapy.…”
Section: Introductionmentioning
confidence: 99%